Implementation of Quality Management in Islamic Education to Create an Excellent Generation Based on Islamic Values (A Study at SD Muhammadiyah 1 Sidoarjo): Implementasi Manajemen Mutu Pendidikan Agama Islam Untuk Mewujudkan Generasi Unggul Berdasarkan Nilai Islam (Studi Pada SD Muhammadiyah 1 Sidoarjo) - Karim, Muhammad Faisol; Rahmawati, Imelda Dian (Indonesian Journal of Innovation Studies, 2026)
General Background Islamic education plays a crucial role in developing human potential through structured religious values and character building. Specific Background Quality management in primary Islamic schools requires systematic implementation across educational inputs, processes, and outputs to meet national standards. Knowledge Gap However, practical strategies for executing quality control and teacher professional development within Islamic elementary education remain insufficiently synthesized. Aims This study analyzes the implementation of Islamic education quality management, school management roles, and influencing factors at SD Muhammadiyah 1 Sidoarjo. Results Findings reveal that quality management centers on output standardization by optimizing educational inputs, enhancing teacher professionalism, and integrating planning, execution, and evaluation cycles. Novelty This study establishes an integrated model connecting teacher competence development with holistic Islamic character cultivation. Implications Institutional managers can leverage these structured management strategies to maintain educational quality and produce excellent generations grounded in Islamic values. Key Findings Highlights Quality management optimizes educational inputs to guarantee standardized graduate outputs. Continuous planning, execution, and evaluation cycles elevate teacher professional standards. Strategic synergy between internal resources and external support strengthens character cultivation. Keywords: Islamic Education, Quality Management, Teacher Professionalism, Primary School, Excellent Generation